Literature Review: LGBT as a Latent Phenomenon Threatening the Morality of the Nation's Generation - Yuniarto budi dwi widiantoro; Nabilatun Nada; Erika Tria Agustina; Damajanti Kusuma (International Conference on Psychology and Education (ICPE), 2025)
The LGBT phenomenon presents a latent threat to the moral integrity of Indonesia’s younger generation. This literature review employs a Systematic Literature Review (SLR) approach to analyze how digital platforms—particularly social networking applications—facilitate the dissemination of non-normative sexual identity values, which conflict with Indonesia's religious, cultural, and moral foundations. The synthesis of relevant studies indicates that exposure to LGBT-related digital content contributes to psychosocial challenges among adolescents, including identity confusion, anxiety, and value disorientation. Digital modeling and social reinforcement mechanisms further accelerate the internalization of values that may erode collective morality. In response, this study emphasizes the critical importance of strengthening digital literacy, character education rooted in national values, and self-regulation among youth to safeguard moral cohesion.